2016
DOI: 10.21608/zumj.2016.4587
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Claudin-1 and S100a4 Expression in Primary Colorectal Carcinoma

Abstract: Background: Metastasis is a major cause of death in colorectal carcinoma (CRC). Epithelial to mesenchymal transition (EMT) plays a role in promoting carcinoma invasion and metastasis. Many molecules are crucial in EMT, including claudin-1 and S100A4. Aim of work: The aim of this study is to assess the pattern of expression and the prognostic significance of claudin-1 and S100A4 in primary colorectal carcinoma. Methods: Claudin-1 and S100A4 expressions were retrospectively analysed by immunohistochemistry in 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…By immunohistochemistry staining of claudin-1 protein, the loss of differentiation ability is characterized by the low claudin-1 expression on high grade or poorly differentiated tumor cells ( Figure E-F). This study result shows there is a significant difference in h-score claudin-1 expression between low-and high-grade adenocarcinoma [8,10,17]. In addition, decreased claudin-1 expression is also related to lymph node metastasis and aggressive behavior [3,9].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…By immunohistochemistry staining of claudin-1 protein, the loss of differentiation ability is characterized by the low claudin-1 expression on high grade or poorly differentiated tumor cells ( Figure E-F). This study result shows there is a significant difference in h-score claudin-1 expression between low-and high-grade adenocarcinoma [8,10,17]. In addition, decreased claudin-1 expression is also related to lymph node metastasis and aggressive behavior [3,9].…”
Section: Discussionmentioning
confidence: 77%
“…Claudin-1 expression in colorectal cancer has been studied. Kaf et al [8] showed that claudin-1 expression was found to be significantly related to histological grade, morphology subtype, tumor invasion depth, and distant metastasis. This finding is in line with those of Ersoz et al [3] and Suren et al [9] On the contrary, Yoshida et al [10] and Hirakawa et al [11] found that there was no significant relationship of claudin-1 expression in higher grade tumor and tumor invasion depth.…”
Section: Introductionmentioning
confidence: 99%